Filsafat Ketuhanan Menurut Baruch de Spinoza - I Wayan Kariarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Philosophy is an attitude towards life and nature. Philosophers use different terminology and points of view in seeing nature according to their respective backgrounds and interests. Spinoza as a philosopher in the 17th century used rationalism and mysticism in conveying his thoughts. Through his philosophy, Spinoza tries to instill an inclusive, pluralist insight into society. With the hope that everyone can live in a society with peace, tolerance, mutual respect for each other's differences and diversity. To be happy, each individual must uphold ethics. Because the goal of ethics is happiness. Happiness is freedom. True freedom is an understanding of various needs which will ultimately be able to free oneself from emotional turmoil that misleads logic. Pantheism is the belief that everywhere is God or every aspect of nature is described as being controlled by God. Pantheism contains various fundamental aspects of harmony that humans need, such as love, brotherhood, tolerance, peace and so on. As much as possible, every individual makes use of the freedom he has in normative ways in order to create welfare for all living things.